A Study of Intercountry Adoption Outcomes in Ireland - GREENE, SHEILA MARY; WHYTE, JEAN; NIXON, ELIZABETH (The Adoption Board, 2007)
The study consisted of three stages. In stage one, research on intercountry adoption outcomes, policies and practices was reviewed. A computerised database on all intercountry adoptions in Ireland was compiled. In stage two, measures were selected and interview schedules constructed. The resulting schedules suited to children from ages 2 to 18, their parents, young adults and teachers were piloted and refined. A random sample of 180 children aged one to 18 was drawn from the total population. In stage three, the main data collection took place, entailing visits to 170 households in order to assess and interview the children and their parents, distribution of questionnaires to 70 teachers, focus groups with service providers, meeting with support groups and interviews with 19 young internationally adopted adults. This report presents an extensive description of the resulting data. The qualitative data have been summarized and every effort has been made to allow the voices of the adoptive parents and children to tell their stories. The quantitative data have been subject to preliminary analysis using a mix of univariate and multivariate statistical procedures
PUBLISHED
Dublin
Keywords: Adoption in Ireland